The paediatric liver transplant experience in Johannesburg, South Africa: A broad overview and update - K Kinandu; A Beeton; M Beretta; S Berkenfeld; L Brannigan; R Britz; D Demopoulos; L Doedens; M Duncan; P Gaylard; C Hajinicolaou; W Lowman; et al. (South African Medical Journal)
Background: